Third-party ATP sensing in polymersomes : a label-free assay of enzyme reactions in vesicular compartments - Yildiz, Umit Hakan (2014)
Submicrometer, porous polymeric vesicles, composed of an amphiphilic di-block copolymer, polystyrene-b-polyisocyanoalanine (2-thiophene-3-yl-ethyl) amide, are used to encapsulate an enzyme, alkaline phosphatase, and a fluorescent reporter polymer poly 1(3((4methylthiophen-3-yl)oxy) propyl) quinuclidin-1-ium. Passive diffusion of exogenously added adenosine triphosphate (ATP) through the membrane was sensed by monitoring the ATP-induced fluorescence quenching of the reporter polymer followed by partial recovery of its emission due to hydrolysis of reporter-bound ATP by alkaline phosphatase.